Examination timetabling problem with scarce resources: a case study - Keskin, Muhammed Emre; Doyen, Alper; Akyer, Hasan; Guler, Mehmet Guray (INDERSCIENCE ENTERPRISES LTD, 2018)
Examination timetabling problem (ETP) is one of the hardest administrative tasks that has to be undertaken at each semester in all faculties. Although the major structure of the problem remains intact, requirements may change from faculty to faculty causing major changes in the solution procedures. The number of academic staff and the level of infrastructures of newly established universities cannot keep up with the increasing number of departments and students. This scarcity brings several additional constraints to the ETP. In this study, we propose a two stage solution procedure for the ETP of such universities. We apply our solution method to a real problem. We show that better feasible solutions can be found in shorter computation times compared to commercial softwares. Moreover we show that the total examination period length can be reduced from seven days to six days with the proposed method.
Keywords: examination timetabling; scarce resources; mixed-integer programming; optimisation; decomposition; two stage solution strategy; heuristic; industrial engineering; COLONY OPTIMIZATION; ALGORITHM; Engineering; Operations Research & Management Science